Ask me again tomorrow a life in progress - Dukakis, Olympia 1931-2021 (HarperCollins, 2003)
The actress offers a straightforward discussion of her life and career, from the ethnic challenges she overcame to her work in such films as "Moonstruck" and "Tales of the City."
Includes bibliographical references
Keywords: Dukakis, Olympia; Dukakis, Olympia -- 1931-2021; Actors -- United States -- Biography; USA; Biografie